The School as a Space for Articulation and Understanding of Coexistence, Citizenship and Transparency. A Look from/La Escuela como Espacio de Articulación y Comprensión de la Convivencia, la Ciudadanía y la Transparencia. Una Mirada desde los Estudiantes (Encuentros, 2019)
A challenge is for educational institutions to promote and develop an inclusive, democratic and participatory education. The objective of this research was to investigate, the representations of basic education students, related to the school coexistence, citizenship and transparency. According to social consensus, they are essential dimensions for building a democratic, participatory and peaceful society. The research is part of a hermeneutic-narrative approach. Semantic networks were applied to 228 students (49% men and 51% women), from fourth to eighth grade, of a public school. The results showed the existence of common narratives such as respect, friendship and honesty. The values, regulations and social characteristics are relevant for coexistence and citizenship. The findings permit to conclude that a good life at school, requires practical recognition to the other, as well as personal and institutional relationships based on the truth. It is invited to articulate these senses for the strengthening of the good manner and the construction of communityKeywords: School convivence; Citizenship; Transparency; Narrative hermeneutic; School.